Sexual Abuse and Lifetime Diagnosis of Somatic Disorders: A Systematic Review and Meta-analysis - Paras, Molly L; Murad, Mohammad Hassan; Chen, Laura P; Goranson, Erin N; Sattler, Amelia L; Colbenson, Kristina M; Elamin, Mohamed B; Seime, Richard J; Prokop, Larry J; Zirakzadeh, Ali (JAMA : the journal of the American Medical Association, 2009)
CONTEXT Many patients presenting for general medical care have a history of sexual abuse. The literature suggests an association between a history of sexual abuse and somatic sequelae. OBJECTIVE To systematically assess the association between sexual abuse and a lifetime diagnosis of somatic disorders. DATA SOURCES AND EXTRACTION A systematic literature search of electronic databases from January 1980 to December 2008. Pairs of reviewers extracted descriptive, quality, and outcome data from included studies. Odds ratios (ORs) and 95% confidence intervals (CIs) were pooled across studies by using the random-effects model. The I2 statistic was used to assess heterogeneity. STUDY SELECTION Eligible studies were longitudinal (case-control and cohort) and reported somatic outcomes in persons with and without history of sexual abuse. RESULTS The search identified 23 eligible studies describing 4640 subjects. There was a significant association between a history of sexual abuse and lifetime diagnosis of functional gastrointestinal disorders (OR, 2.43; 95% CI, 1.36-4.31; I2 = 82%; 5 studies), nonspecific chronic pain (OR, 2.20; 95% CI, 1.54-3.15; 1 study), psychogenic seizures (OR, 2.96; 95% CI, 1.12-4.69, I2 = 0%; 3 studies), and chronic pelvic pain (OR, 2.73; 95% CI, 1.73-4.30, I2 = 40%; 10 studies). There was no statistically significant association between sexual abuse and a lifetime diagnosis of fibromyalgia (OR, 1.61; 95% CI, 0.85-3.07, I2 = 0%; 4 studies), obesity (OR, 1.47; 95% CI, 0.88-2.46; I2 = 71%; 2 studies), or headache (OR, 1.49; 95% CI, 0.96-2.31; 1 study). We found no studies that assessed syncope. When analysis was restricted to studies in which sexual abuse was defined as rape, significant associations were observed between rape and a lifetime diagnosis of fibromyalgia (OR, 3.35; 95% CI, 1.51-7.46), chronic pelvic pain (OR, 3.27; 95% CI, 1.02-10.53), and functional gastrointestinal disorders (OR, 4.01; 95% CI, 1.88-8.57). CONCLUSION Evidence suggests a history of sexual abuse is associated with lifetime diagnosis of multiple somatic disorders.